2020
DOI: 10.1155/2020/1854363
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Treatment Suppresses Transcription Factor IRF8 in Spinal Cord of Rats with Spared Nerve Injury

Abstract: Objective. Neuropathic pain with complex mechanisms has become a major public health problem that greatly impacts patients’ quality of life. Therefore, novel and more effective strategies against neuropathic pain need further investigation. Electroacupuncture (EA) has an ameliorating effect on neuropathic pain following spared nerve injury (SNI), but the underlying mechanism remains to be fully clarified. Interferon regulatory factor 8 (IRF8), a critical transcription factor, was reported to be involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Experiments demonstrated that EA stimulation has an inhibitory effect on mechanical hypersensitivity in spinal nerve ligation (SNL) rats [ 9 , 35 ]. In the previous research, we also found that EA can regulate the activation of microglia in the spinal cord of SNI rats, thereby affecting the release of inflammatory cytokines and inhibiting pain-related signaling pathways [ 23 , 29 , 36 ]. Study showed that EA can promote neuroplasticity by increasing neurotrophic factors in the spinal cord [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments demonstrated that EA stimulation has an inhibitory effect on mechanical hypersensitivity in spinal nerve ligation (SNL) rats [ 9 , 35 ]. In the previous research, we also found that EA can regulate the activation of microglia in the spinal cord of SNI rats, thereby affecting the release of inflammatory cytokines and inhibiting pain-related signaling pathways [ 23 , 29 , 36 ]. Study showed that EA can promote neuroplasticity by increasing neurotrophic factors in the spinal cord [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microglia are the most important glial cells. EA downregulates microglial chemokine receptor (CX3CR1) expression, inhibits microglia activation, and reduces central neuro-inflammation pain by inhibiting TLR4/MyD88 co-expression and NF-κB p65 activation ( 18 , 28 , 33 ). Some findings suggest that inhibition of microglia activation by acupuncture may be associated with reduced cyclooxygenase-2 (COX-2) expression in spinal cord ( 40 ).…”
Section: Mechanism Of Action Of Acupuncture In the Treatment Of Neuro...mentioning
confidence: 99%
“…The doses reported ranged from 1 to 2 mA, fluctuating between 2 and 100 Hz, 1.05 to 2.85 milli seconds for 30 minutes. Most of the changes seem to occur in the dorsal horn [75][76][77][78][79][80] although changes in the nerve, 81,82 blood, 83 and DRG 84 were also reported. In contrast, four articles did not find changes in cytokine concentrations following electroacupuncture.…”
Section: Physical Agentsmentioning
confidence: 99%